(untitled) (Global Journal of Human-Social Science, 2018)
A member of Institute of African Culture and International Understanding IACIU Centre for Human Security in Africa CHS His Excellency Olusegun Obasanjo Presidential Library OOPL UNESCO United Nation 1Learners have different views for learning and doubt the usual phenomenon that is expected by all admitted in schools It is defined by the Oxford dictionary as the process of gaining knowledge through experience teaching and study This learning defined has specific terms in the defining We have knowledge experience Teaching and study These specifics take time before they are understood by learners and the objective with which they are in school is achieved Learners do not understand the reasons for being in school All they know is to see a teacher for some writing skills and reading and at the end tested to see who is the best in class It is not the case for the real meaning of learning in schools